Metabolic profiling of endophytic fungi acting as antagonists of the banana pathogen Colletotrichum musae - Christian Joseph R. Cumagun; Joden M. Adiova; Ruth Jakobs; Anna Rathgeb; Petr Karlovsky; Caroline Muller (PLoS ONE, 2025)
Three endophytic strains, Phomopsis sp., Fusarium proliferatum, and Tinctoporellus epimiltinus, isolated from various plants in the rainforest of the Philippines, were investigated regarding their ability to repress growth of the pathogenic fungus Colletotrichum musae on banana fruits causing anthracnose disease. An in vitro plate-to-plate assay and an in vivo sealed box assay were conducted, using commercial versus natural potato dextrose medium (PDA). All tested endophytes were able to significantly reduce C. musae growth compared to the control. However, the type of medium had no significant effect on lesion size of C. musae on banana. An interaction effect between fungal strain and medium could be shown. On the commercial medium, no differences between the biocontrol ability of the fungi and control treatments could be found, while there were significant differences between the fungal strains on natural medium. Lesions on banana incubated with Phomopsis sp. on natural medium were significantly but only slightly larger than those on banana incubated with F. proliferatum. Volatiles released by these two strains and one pathogenic strain of F. graminearum were collected using polydimethylsiloxane tubes and analyzed via gas chromatography mass spectrometry (GC-MS). Twelve volatile metabolites were detected. Benzaldehyde was the most prominent volatile emitted from the commercial and plain medium. 2-Undecanone, 2-nonanone, and phenylethyl-alcohol were detected in individual samples in both media. 1-Decanol and acoradiene were exclusive to the commercial medium, with acoradiene also being unique to F. proliferatum. Five volatileorganic compounds (VOCs)were emitted from all tested fungal species: 2-heptanone, 2-nonanone, 2-undecanone, 2-tridecanone, and phenylethyl-alcohol. Beta-acorenol was detected in F. proliferatum grown on both media. To reveal whether the medium (commercial PDA versus potato extract) affected the metabolism of the fungi, metabolic footprints were assessed via high performance liquid chromatography with quadrupole time of flight mass spectrometry MS (HPLC-QTOF-MS). A total of 388 metabolic signals were recorded. The intensities of 80–90% of these signals differed significantly between the two types of media. Metabolic footprints varied in response to different potato dextrose medium preparations. The two promising fungal strains may be used to reduce postharvest decay and losses in fruits.